Coffee pruning and differents irrigation periods: productivity and quality - Conceição Rezende, Fátima; Resende Arantes, Kelte; dos Reis Oliveira, Sérgio; Alves de Faria, Manoel (Coffee Science - ISSN 1984-3909, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif]–>An experiment was carried out in Lavras/MG aiming to evaluate the effects of different irrigation periods on total yield, volumetric yield, and bean ripening uniformity from coffee (Coffea arabica L.) (Cv. Topazio, MG1190) that was submitted to a severe pruning 65 months after planting. The orchard was implanted in 1.8 x 0.7m spacing and was drip irrigated. A complete randomized experimental design with six treatments and four replications was implemented. Treatments corresponded to six different irrigation periods. Applied irrigation depth was equivalent to 100% of the balance including the evaporation depth from a class “A” pan and the precipitation depth measured during the time interval between two successive irrigations (ECA-P). Fertilization with nitrogen and potassium was split in 4 applications under canopy throughout the period from October to March. Data from the 2002/2003 2003/2004 harvest, were analyzed. Results indicated that accumulated productivity tends to be larger under the treatments receiving irrigation from April to July but retard coffee bean maturation. Irrigation increases the volumetric yield. Coffee quality (bean size and defects) from the first harvest was better than second harvest.